Studi Literatur: Karakteristik Perkembangan Peserta Didik di Sekolah Dasar - Zaenurrozikin, Muhammad; Usriyah, Lailatul; Mua’limin, Mua’limin (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2025)
Child development during the elementary school period includes various aspects, such as cognitive, social, emotional, physical, and language. language. Although each child develops in a unique way, there are some common some common developments that can be identified in children aged 6 to 12 years. years. On the physical aspect, children experience rapid body growth, and the development of fine and gross motor skills. The purpose of this study is to examine more deeply the developmental characteristics of children during the elementary school period. This research uses the literature study method (library research). The development of primary school-age children (6-12 years old) includes three main aspects motor, cognitive, and socio-emotional aspects. In the motor aspect, children physical coordination, both fine and gross motor, which supports learning activities. support learning activities. In the cognitive aspect, children's thinking ability develop from the imaginative stage to a concrete and rational mindset, enabling them to complete intellectual tasks effectively. Meanwhile, in the socio-emotional aspect, children begin to build independence from the family, strengthening relationships with friends and family from the family, strengthen relationships with peers, and develop self-concept and self-confidence. self-concept and self-confidence. The social environment plays an important role in the formation of character and behavior. A thorough understanding of these developmental characteristics is necessary for teachers to apply the right approach to education in order to support children's optimal development in various aspects.